STUDY OF SODIUM, POTASSIUM, AND CALCIUM SALTS INFLUENCE ON PROTEIN STABILITY BY DIFFERENTIAL SCANNING CALORIMETRY - E. K. Tunieva; I. Dederer (Теория и практика переработки мяса, 2016)
Abstract Study of protein stability depending on the various technological factors allows to directionally adjust the physicochemical properties of raw meat and the quality of finished meat products. The paper investigates the possibility of using the DSC to study the influence of monovalent and divalent salts on protein thermal stability. In order to determine the effect of sodium chloride and its substitutes, potassium and calcium salts, on the thermal stability of proteins, the studies were carried out with grinded pork longissimus muscle samples salted with sodium chloride at level of 2.0% and with salt compositions containing reduced by 50% level of sodium chloride (a mixture of sodium and potassium chlorides; a mixture of sodium, potassium, and calcium chlorides) using the differential scanning calorimeter DSC Q 2000 in the temperature range of 5 °C to 100 °C and the temperature change rate of 1 K/min. It was found that the addition of potassium chloride instead of 50% of sodium chloride had no significant effect on actin and myosin resistance to thermal denaturation. Meat salting using the mixture of sodium, potassium, and calcium chlorides resulted in decrease of myofibrillar proteins stability indicating the destabilizing effect of calcium on actin and myosin. A negative correlation between the magnitude of the ionic strength and the temperature of myosin and actin denaturation has been found. The correlation coefficients were minus 0.99 and minus 0.95 for myosin and actin respectively. Reduction of denaturation temperature for myofibrillar proteins in the presence of calcium chloride opens perspectives to study the possibility of heat treatment at lower temperatures for meat products with reduced sodium content.